Kajian Psikologis Akan Harapan Dan Keputusasaan Dalam Novel “The Old Man And The Sea” Karya Ernest Hemingway - ahmad muhid (Universitas Aki, 2016)
Life is frequently filled with hope and despair for one reason or another. The similar circumstances occur within Santiago’s self. Old Santiago as the protagonist of the story experiences despair when he stumbles upon hardships and difficulties on his ocean’s voyage. His conflict is not against other characters but against nature instead. On one hand, he must fight against ocean’s roaring big wave and menacing gigantic shark that is following him during his fish catching. This condition makes him in despair. On the other hand, his hopes come when remembers his God; besides his enjoyment on making friendship with birds following and greeting him in sailing boat. Santiago is a tough sailor and he psychologically is a sanguine and choleric type of person. He is warm and friendly. Besides that he is also open, extrovert and enthusiastic kind of character. As a sanguine he enjoys on whatever God has bestowed upon him. He is insistent on his voyage although his friends remind him with a phrase “salao” that means bad luck. He is not afraid of the so-called bad luck, to him he has motto: ever onward, no retreat. Keywords: hope and despair, sailing boat, sanguine, kholeric, conflict, nature